2011
DOI: 10.1007/s13277-011-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

SPARCL1: a potential molecule associated with tumor diagnosis, progression and prognosis of colorectal cancer

Abstract: Background: Accumulating evidence has shown that cancers are the results of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 17 publications
5
28
1
Order By: Relevance
“…Whether SPARCL1 plays protective role in rectal cancers awaits further confirmation. A Swedish research team reported that SPARCL1 was positively associated with well differentiation, which is consistent with our findings (19). However, their patient-based data indicated that SPARCL1 prognosticates poor survival in CRCs (19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whether SPARCL1 plays protective role in rectal cancers awaits further confirmation. A Swedish research team reported that SPARCL1 was positively associated with well differentiation, which is consistent with our findings (19). However, their patient-based data indicated that SPARCL1 prognosticates poor survival in CRCs (19).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, pilot studies showed that high SPARCL1 expression level is associated with welldifferentiated status, less metastasis, and better survival in CRCs (18). Similar results were obtained by other investigators that indicated that the expression of SPARCL1 increased with greater level of differentiation and decreased in progressing from Dukes stage B to D. However, their data showed that expression of SPARCL1 led to poor survival in CRCs (19). Therefore, the prognostic value of SPARCL1 needs to be further investigated at multiple centers with larger population.…”
Section: Introductionsupporting
confidence: 75%
“…16). The almost exclusive expression of SPARCL1 in ECs was the subject of controversy in previous studies (24,39). However, our results are strongly supported by the consistent confirmation we obtained with 3 different methods (permanent IHC, immunofluorescence IHC, and ISH) and the agreement with studies by others in humans and mouse models (11,57,58).…”
Section: Discussionsupporting
confidence: 91%
“…SPARCL1 is described as an antiadhesive protein (38) that exerts antitumorigenic activity specifically in CRC if recombinantly expressed in or added as a purified protein to RKO or SW620 cell lines (24,37). As yet in CRC tissues, SPARCL1 expression has been detected in CRC tissues, but conflicting results exist with respect to its presence in tumor cells and/or ECs, and, as such, its association with prognosis is a subject of controversy (24,39). As yet, nothing is known about the regulation or induction of SPARCL1 expression or its functional impact on vessel phenotype in human carcinomas.…”
Section: 2mentioning
confidence: 99%
“…Particularly, growing evidence shows that SPARCL1 often presents a reduced or absent expression pattern in a variety of human tumor tissues (Bendik et al, 1998;Nelson et al, 1998;Isler et al, 2004;Esposito et al, 2007;Zaravinos et al, 2011;Hurley et al, 2012;Li et al, 2012). However, several studies have also found that an increased expression of SPARCL1 in a few of other type of human tumors derived from liver (Lau et al, 2006), uterus (Mencalha et al, 2008), and colon and rectum (Zhang et al, 2011;Hu et al, 2012). All these conflicting findings suggest that SPARCL1 is indeed implicated in human cancer development and progression, but its expression pattern may be in a tissue-specific manner.…”
Section: Discussionmentioning
confidence: 99%